2001
DOI: 10.1097/00000542-200111000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Intubating LMA-Fastrach™  in 254 Patients with Difficult-to-manage Airways

Abstract: The LMA-Fastrach was used successfully in a high percentage of patients who presented with a variety of DA. The clinical experience presented herein indicates that this device may be particularly useful in the emergency and elective treatment of patients in whom intubation with a rigid laryngoscope has failed and in the treatment of patients with immobilized cervical spines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
2
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(200 citation statements)
references
References 20 publications
10
176
2
12
Order By: Relevance
“…Unfortunately, the success rate of FOBassisted intubation through the FT-LMA is less predictable following a failed blind technique in patients with a difficult airway. While Ferson et al reported a 100% success rate of FOB-assisted intubation through the FT-LMA (seven of the seven patients), 11 Joo et al reported a success rate of only 50% (five of the ten patients). 31 …”
Section: Use Of the Airway Exchanger Cathetermentioning
confidence: 96%
See 3 more Smart Citations
“…Unfortunately, the success rate of FOBassisted intubation through the FT-LMA is less predictable following a failed blind technique in patients with a difficult airway. While Ferson et al reported a 100% success rate of FOB-assisted intubation through the FT-LMA (seven of the seven patients), 11 Joo et al reported a success rate of only 50% (five of the ten patients). 31 …”
Section: Use Of the Airway Exchanger Cathetermentioning
confidence: 96%
“…B Before blind intubation or intubation assistance with an EschmannÒ Tracheal Tube Introducer (gum elastic bougie) or with an airway exchanger catheter (AEC), the FT-LMA is slightly lifted (but not tilted) away from the posterior pharyngeal wall using the metal handle. This ''second'' maneuver prevents the endotracheal tube (ETT) from impacting the arytenoids or vestibule of the larynx and helps guide the passage of an ETT, bougie, or AEC into the trachea 11 The Fastrach TM Intubating Laryngeal Mask AirwayÒ: an overview and update 591 57% with clockwise or counterclockwise manipulation. However, they also compared the use of the relatively inexpensive Parker Flex-Tip ETT (Parker Medical, Highlands Ranch, CO, USA) with a posterior opening bevel and achieved a success rate similar to that of a PVC ETT after the first attempt (54% vs 48%, respectively), which increased to 86% after manipulation 15 ( Figure 4).…”
Section: Endotracheal Tube Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cords may act like unidirectional valves that offer resistance to pressure, provided by the flow of gases during forced inspiration. 2 In Hemmerling's report, flow volume is not mentioned. We hypothesize that with higher gas flows during IPPV, there is a greater propensity to involuntary vibration and irritation of the un-paralyzed vocal cords which may lead to further irritation and potential injury.…”
Section: Air Humidification Might Help To Prevent Irritation and Damamentioning
confidence: 99%